Strategi Komunikasi Humas Polres Sikka Pada Website Tribratanewssikka.com Dalam Meningkatkan Citra Institusi - Maria Anselmia; Viktor Ariestyan Sedu; Markus Kristian Retu (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2026)
This study aims to analyze the communication strategy of the Public Relations division of Sikka Police Resort through the TribrataNewsSikka.com website in enhancing institutional reputation and online image management. This research is situated within the field of Communication Studies, focusing on Cyber Public Relations, particularly on reputation building and online image management of public institutions. The study employs a qualitative descriptive method. Data were collected through website content observation, interviews with public relations officers, and documentation of digital publications. Data analysis was conducted by linking the findings to Cyber Public Relations principles, including information management, message consistency, transparency, and responsiveness in shaping a positive online image. The results indicate that TribrataNewsSikka.com functions as a strategic digital platform for strengthening institutional reputation by disseminating information on police activities, public services, and issue clarification to maintain public trust. Nevertheless, enhancing interactivity and two-way communication remains necessary to optimize online image management.